Geopolitics of post-liberal world One Belt and One Road initiative of China and the involvement of Azerbaijan - Valiyeva, Raisa (ADA University, 2019)
This study discusses “One Belt and One Road Initiative” (BRI) of China from the geopolitical perspective and find out the pros and cons for the involvement of Azerbaijan in this project from the perspective of the debt-trap diplomacy. It starts with introducing the content and context of BRI followed by the literature review part that presents various approaches towards BRI, discussing its implementation in different regions. It particularly focuses on such variables as current geopolitical situation, the economic situation, and other features which are important for China (i.e., demand for raw materials, especially the hydrocarbon resources).
Keywords: Public and International Affairs; Geopolitics; Geopolitics--Azerbaijan; Energy Geopolitics--Azerbaijan; Energy security